The Simulation on Vehicular Traffic Congestion Using Discrete Event Simulation (DES): A Case Study - Noor Akma, Abu Bakar; Khalid, Adam; Ainil Fahsha, Nasrun Adi; Younis, Younis M.; Mazlina, Abdul Majid; Fakhreldin, M. (IEEE, 2018)
The bottleneck networks of the vehicular traffic flow required the clear understanding and the insights of congestion factors, determines the time and location of traffic breakdown. The congestion propagates through the network caused by the numbers of vehicles continuously growing. There have been lots of research studies to resolve the issues. Simulation and modelling to the related issues seem significance to the operational research specifically the traffic flow dynamic for the design, analysis and the management. Hence, this work focused on a simulation model for the vehicular traffic flow in order to reduce the traffic congestion for a smooth and low-density traffic flow system. Three scenarios from a traffic flow system based on queuing environment which is current traffic flow system as S1, the newly proposed models as S2 and S3 have been suggested to improve the traffic flow of the intersection. The method of comparing the performance of simulation results and difficulties, alternative road, the predictive strategy as decision support model with the potential alternative road has been identified with developing traffic flow simulation using Discrete Event Simulation (DES). DES is as the well-known traditional approach to catering the problems regarding the queuing system and run simulation models on the different traffic scenarios for bottleneck analysis. The lower values for the cumulative average all the parameters indicated the traffic congestion is decreased and to avoid the traffic jam. The experimental results and statistical analysis showed that the proposed simulation model S2 and S3 for vehicular traffic flow is better than the current traffic flow system S1. It can be summarized that model 3 (S3) can be applied to the new vehicular traffic flow system with the better simulation results has been produced from the experimental simulations.